The joint use of ABC/VEN analysis and the Beers criteria for optimizing expenditure of funds and rational prescribing of medications to elderly patients - O. A. Makhmudova; G. F. Avkhadieva; O. G. Bagdanova; V. N. Khaziakhmetova (Фармакоэкономика)
Objective: to conduct a pharmacoeconomic evaluation of the rationality of prescribing medications and to analyze the frequency of prescribing potentially inappropriate medications to patients over 65 years old using the example of additional preferential drug provision.Material and methods. The analysis was based on registers of medications dispensed within the framework of additional drug provision over 2019–2021 period. We conducted an integrated study combining ABC/VEN analysis and the Beers criteria to assess the rationality of pharmacotherapy.Results. The analysis of the cost structure for medicines showed a positive trend in the distribution of categories V, E, N (vital, essential, nonessential) in A, B, C groups. In 2019, 13.7% of the budget was spent on the procurements of drugs of N category; in 2020, this indicator was 10.6%; and in 2021, the costs for the procurements of drugs of N category decreased to 2.6%. Expenditures for drugs in V and E categories increased from 86.3% to 97.4%. The prevalence of polypragmasy (prescription frequency of 5 or more drugs with different international nonproprietary names per patient for month) among patients over 65 years old reached 11% in 2019, 13% in 2020, and 1% in 2021. According to the Beers criteria, patients over 65 years old were prescribed potentially inappropriate drugs according to the Beers criteria in 12.03% of cases in 2019, in 10.84% of cases in 2020, and in 9.7% of cases in 2021.Conclusion. Due to comprehensive ABC/VEN analysis and the Beers criteria tool it was possible to evaluate the rationality of expenditures on additional drug provision over the period from 2019 to 2021, as well as the rationality of prescribing medications to patients over 65 years old. The use of Beers criteria enables to optimize pharmacotherapy in elderly patients.